2013
DOI: 10.1364/oe.21.031800
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wavelength Brillouin-Raman fiber laser utilizing enhanced nonlinear amplifying loop mirror design

Abstract: We demonstrate a single-spacing, multi-wavelength Brillouin-Raman fiber laser utilizing an enhanced cavity of nonlinear amplifying loop mirror. In this structure, the optimization of multi-wavelength lasing is done with proper adjustments of coupling ratio and Brillouin pump power. When setting the Raman pump power to 300 mW, up to 28 channels with an average 17 dB optical signal-to-noise ratio are achieved. In this case, the Brillouin pump power is maintained at -2.6 dBm when the splitting ratio and Brillouin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The BP source is used to initiate the Brillouin cascaded process based on the SBS phenomenon [11], whereas the Raman pump source is used to convert the optical fiber from loss medium to gain medium based on the SRS phenomenon [12]. Several studies have examined the importance of the effect of Raman pump power (RPP) and Brillouin pump power (BPP) on the performance parameters of the MBRFL system [13][14][15][16]. These studies reported that the RPP affects the MBRFL performance parameters in terms of the intensity of Brillouin Stokes lines (BSLs), power level fluctuations between neighboring channels, flatamplitude bandwidth, optical signal-to-noise ratio of the generated channels, and the SBS threshold power.…”
Section: Introductionmentioning
confidence: 99%
“…The BP source is used to initiate the Brillouin cascaded process based on the SBS phenomenon [11], whereas the Raman pump source is used to convert the optical fiber from loss medium to gain medium based on the SRS phenomenon [12]. Several studies have examined the importance of the effect of Raman pump power (RPP) and Brillouin pump power (BPP) on the performance parameters of the MBRFL system [13][14][15][16]. These studies reported that the RPP affects the MBRFL performance parameters in terms of the intensity of Brillouin Stokes lines (BSLs), power level fluctuations between neighboring channels, flatamplitude bandwidth, optical signal-to-noise ratio of the generated channels, and the SBS threshold power.…”
Section: Introductionmentioning
confidence: 99%
“…The group velocity dispersions (GVD) of the EDF and SMF are 61.2 ps 2 km −1 and −22.9 ps 2 km −1 , respectively. The total GVD of this cavity is estimated to be +0.008 ps 2 ± 0.006 ps 2 , which reveals that it is operating in the stretched-pulse regime. In this scheme, we utilize a single PC instead of the PC-PDI-PC sandwich structure to accomplish mode-locking and wavelength filtering.…”
Section: Experimental Setup and Operation Principlementioning
confidence: 91%
“…Multi-wavelength erbium-doped fiber lasers (EDFLs) have attracted intensive interest due to their potential application in wavelength division multiplexed (WDM) fiber-communication systems, optical fiber sensors, optical instrument testing and THz generation. Various methods have been employed to realize room-temperature multi-wavelength fiber lasers such as introducing four-wave mixing in nonlinear fibers [1], exploiting Brillouin-Raman or Brillouin-erbium fiber lasers [2,3], utilizing the polarization hole burning effect in gain media [4] or a frequency-shifted feedback technique in a laser cavity [5], employing high nonlinear fibers [6,7] and so forth. On the other hand, to attain multi-wavelength operation, a multi-channel filter should usually be used, including a fiber Bragg grating based Fabry-Perot (FP) filter [8], a twin-core fiber-based Mach-Zehnder interferometer [9], Sagnac loop mirrors with polarization-maintaining fiber (PMF [10]), or a birefringence fiber filter [11].…”
Section: Introductionmentioning
confidence: 99%
“…Erbium-doped fiber (EDF) lasers have attracted a great deal of research interest due to their wide applications in fiber sensors and communications [1][2][3][4][5][6][7][8][9]. They can deliver a continuous wave (e.g.…”
Section: Introductionmentioning
confidence: 99%